Ammonia decomposition catalyst and ammonia decomposition method
By developing a porous catalyst containing ruthenium, lanthanum, aluminum and cerium, the problem of low efficiency of existing ammonia decomposition catalysts is solved, and high-efficiency ammonia decomposition and low-cost hydrogen production are achieved.
Patent Information
- Application Number
- CN202480003425.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-07-25
- Filing Date
- 2024-02-13
- Publication Date
- 2025-03-11
AI Technical Summary
The existing ammonia decomposition catalysts are inefficient, resulting in high hydrogen production costs and inappropriate porosity and pore size distribution of the catalyst, which affects the reaction efficiency.
An ammonia decomposition catalyst is developed including a support and a catalytically active component supported on the support, which comprises ruthenium, lanthanum, aluminum and cerium, with a porosity of more than 25% and an appropriate pore size distribution.
The efficiency of ammonia decomposition reaction is improved, the cost of hydrogen production is reduced, the life of the catalyst is extended, and the gas flow stability in the reactor is optimized.
Smart Images

Figure CN119604360A_ABST
Abstract
Description
Technical Field
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims the benefit of Korean Patent Application No. 10-2023-0018962 filed on February 13, 2023, and Korean Patent Application No. 10-2023-0096826 filed on July 25, 2023, in the Korean Intellectual Property Office, the disclosures of which are incorporated herein by reference in their entirety.
[0003] The present disclosure relates to an ammonia decomposition catalyst and an ammonia decomposition method. Background Art
[0004] Recently, as interest in the environment and energy has increased, issues regarding the hydrogen economy are also expanding.
[0005] The hydrogen economy refers to an economic industrial structure that uses hydrogen as the main energy source. In other words, it refers to an economic system that moves away from the current energy system centered on fossil fuels, increases the use of hydrogen as an energy source for power generation systems, heat generation systems, machinery such as automobiles, and creates new industries and markets in all areas required for stable production, storage, and transportation of hydrogen.
[0006] In such a system, water can be produced by various means such as water electrolysis, natural gas reforming, gasification of biomass, and can be distributed or transported to hydrogen fuel cells through a pipeline network, but due to the high cost and risk of direct transportation of hydrogen, there is a growing interest in technologies that can easily and safely transport hydrogen at a low price.
[0007] One of the methods to efficiently store and transport hydrogen is to transport ammonia, decompose the transported ammonia and use it as a hydrogen source.
[0008] Since the reaction for decomposing ammonia into hydrogen and nitrogen is an endothermic reaction with a large energy difference, and the activation energy of the reaction is also very high, a large amount of energy is required to obtain a useful amount of hydrogen as a product, so the production cost of hydrogen is high.
[0009] Therefore, research on ammonia decomposition catalysts with high ammonia decomposition efficiency has attracted more and more attention. Summary of the invention
[0010] Technical issues
[0011] An object of the present invention is to provide an ammonia decomposition catalyst having high ammonia decomposition efficiency.
[0012] Another object of the present invention is to provide a method for decomposing ammonia using the ammonia decomposition catalyst.
[0013] Technical Solution
[0014] According to the present disclosure, an ammonia decomposition catalyst is provided, comprising: a carrier and a catalytically active component supported on the carrier, wherein the catalytically active component comprises i) ruthenium (Ru) as a first metal; ii) lanthanum (La) as a second metal; and iii) one or more of aluminum (Al) and cerium (Ce) as a third metal, and the catalyst has a porosity of more than 25%.
[0015] According to one embodiment, the ammonia decomposition catalyst may have a porosity of about 20% or more, or about 30% or more, and about 50% or less, or about 45% or less.
[0016] According to one embodiment, the median value of the pore size of the ammonia decomposition catalyst may be about 50 μm to 150 μm. More specifically, the median value of the pore size of the ammonia decomposition catalyst may be about 50 μm or more, or about 70 μm or more, or about 80 μm or more, or about 100 μm or more, or about 110 μm or more, and about 150 μm or less, or about 140 μm or less, or about 130 μm or less.
[0017] According to one embodiment, the support may be an inorganic oxide structure. More specifically, the inorganic oxide may be an inorganic oxide containing one or more elements selected from silicon, zirconium, aluminum and cerium.
[0018] According to one embodiment, the first metal may be included in an amount of: about 0.01 parts by weight to about 0.5 parts by weight; or more than about 0.01 parts by weight, or more than about 0.05 parts by weight, or more than about 0.1 parts by weight, and less than about 0.5 parts by weight, or less than about 0.4 parts by weight, or less than about 0.35 parts by weight, or less than about 0.3 parts by weight, based on 100 parts by weight of the carrier and the catalytically active component.
[0019] According to one embodiment, the catalytically active component may be included in an amount of: about 20 parts by weight or less; or about 0.1 parts by weight or more, or about 0.5 parts by weight or more, or 1 part by weight or more, and about 20 parts by weight or less, less than about 18 parts by weight, or about 15 parts by weight or less, or about 12 parts by weight or less, based on 100 parts by weight of the carrier and the catalytically active component.
[0020] According to one embodiment, the weight ratio of (second metal): (third metal) can be: about 1:99 to about 3:7; or about 1:99 or more, or about 2:98 or more, or about 3:97 or more, and about 3:7 or less, or about 25:75 or less.
[0021] According to one embodiment, the first metal may be included in an amount of: about 0.1 wt % to about 10 wt %; or about 0.1 wt % or more, or about 0.5 wt % or more, or about 1.0 wt % or more, or about 1.5 wt % or more, and about 10 wt % or less, or about 7 wt % or less, or about 5 wt % or less, or about 3 wt % or less, based on the total weight of the catalytically active component.
[0022] According to one embodiment, the ammonia decomposition catalyst may be in the form of a hollow cylinder.
[0023] According to one embodiment, the diameter of the circular cross-section of the hollow cylinder can be: about 1 mm to about 10 mm; or about 1 mm or more, 2 mm or more, or about 3 mm or more, or about 4 mm or more, and about 10 mm or less, or about 8 mm or less, or about 7 mm or less, or about 6 mm or less.
[0024] According to one embodiment, the diameter of the hollow may be 0.1 to 0.5 of the diameter of the circular cross section of the cylinder.
[0025] According to one embodiment, the support may include a substrate including alumina and a silica layer formed on the alumina, and the catalytically active component may be contained in the catalyst layer formed on the silica layer.
[0026] According to the present disclosure, there is also provided an ammonia decomposition method, which comprises carrying out a decomposition reaction of ammonia in the presence of any of the above-mentioned ammonia decomposition catalysts.
[0027] According to one embodiment, the ammonia decomposition may be carried out at a temperature of about 400°C to about 550°C; or above about 400°C, or greater than about 400°C, or above about 420°C, and below about 600°C, or below about 550°C, or below about 530°C.
[0028] As used herein, the terms “first”, “second”, etc. are used to explain various components, and they are used only to distinguish one component from other components.
[0029] Furthermore, the terminology used herein is for explaining particular embodiments only and is not intended to be limiting of the present invention.
[0030] Unless the context clearly indicates otherwise, a singular expression includes a plural expression.
[0031] As used herein, the terms "comprising", "equipped with" or "having" are intended to specify the presence of implemented features, numbers, steps, components or their combinations, and are not intended to exclude the possibility of the presence or addition of one or more other features, numbers, steps, components or their combinations.
[0032] In addition, in the case where it is explained that each layer or element is formed “on” or “over” each layer or element, this means that each layer or element is formed directly over each layer or element, or other layers or elements may be additionally formed between the layers or on the object or substrate.
[0033] Although various modifications can be made to the present invention and the present invention can have various forms, specific embodiments will be described and explained in detail below. However, it should be understood that they are not intended to limit the present invention to specific disclosures, and the present invention includes all modifications, equivalents or replacements thereof without departing from the concept and technical scope of the present invention.
[0034] As used herein, a hollow cylinder refers to a cylindrical shape in which a hole in the shape of a smaller cylinder passing through the center of the cylinder is formed, and a circle, a cylinder, etc. do not necessarily mean a mathematically precise shape.
[0035] Figure 1 The shape of a hollow cylinder of a catalyst according to one embodiment of the present invention is schematically shown.
[0036] Reference Figure 1 , the hollow cylindrical shape can be confirmed.
[0037] According to one aspect of the present invention, an ammonia decomposition catalyst is provided, comprising: a carrier and a catalytically active component supported on the carrier, wherein the catalytically active component contains i) ruthenium (Ru) as a first metal; ii) lanthanum (La) as a second metal; and iii) one or more of aluminum (Al) and cerium (Ce) as a third metal, and the catalyst has a porosity of more than 25%.
[0038] The inventors of the present disclosure have found that when a catalytically active component is supported on a carrier of a specific shape to prepare a catalyst having specific pore characteristics, such a catalyst can achieve very high efficiency as an ammonia decomposition catalyst, and have completed the present invention.
[0039] The decomposition of ammonia can be represented by the following reaction formula.
[0040]
[0041] This reaction is a reversible process and can produce 3 molecules of hydrogen from 2 molecules of ammonia. Generally, if the reaction is carried out under high temperature and high pressure conditions in the presence of a catalyst, the forward reaction can prevail, so all the ammonia can be decomposed, leaving a trace amount of undecomposed ammonia.
[0042] However, since the forward reaction is an endothermic reaction, the energy difference between the products and reactants is large, the activation energy of the reaction is high, the reaction efficiency is not high, and a large amount of energy is required.
[0043] Therefore, according to an embodiment of one aspect of the present invention, an ammonia decomposition catalyst is used, which includes: a carrier and a catalytically active component supported on the carrier, wherein the catalytically active component contains i) ruthenium (Ru) as a first metal; ii) lanthanum (La) as a second metal; and iii) one or more of aluminum (Al) and cerium (Ce) as a third metal, and has a porosity of more than 25%.
[0044] As the catalytically active component, ruthenium, lanthanum, aluminum, cerium, etc. can be used in the form of a composite metal oxide. The composite metal oxide refers to a compound or mixture in which two or more metal elements mentioned as the catalytically active component are mixed with the same or different oxidation numbers.
[0045] Among such catalytically active components, ruthenium is known as the metal that directly mediates the reaction, while lanthanum, aluminum and cerium can act as a co-catalyst.
[0046] In addition, in one embodiment, the ammonia decomposition catalyst according to one aspect of the present invention has a porous shape with a porosity of 25% or more. By using a porous catalyst, the surface area of the catalytically active material that can contact the reactants can be increased, and the thermal aggregation of the catalytically active material can be prevented, thereby increasing the life of the catalyst.
[0047] According to one embodiment, the ammonia decomposition catalyst may have a porosity of about 20% or more, or about 30% or more, and about 50% or less, or about 45% or less.
[0048] If the porosity is too low, the reactant, i.e., ammonia, may not contact the catalytically active components present within the catalyst structure, and thus, the efficiency of the ammonia decomposition reaction may be reduced, and if the porosity is too high, the strength of the catalyst may decrease, resulting in deteriorated performance.
[0049] According to one embodiment, the median value of the pore size of the ammonia decomposition catalyst may be about 50 μm to about 150 μm. More specifically, the median value of the pore size of the ammonia decomposition catalyst may be about 50 μm or more, or about 70 μm or more, or about 80 μm or more, or about 100 μm or more, or about 110 μm or more, and about 150 μm or less, or about 140 μm or less, or about 130 μm or less.
[0050] If the median value of the pore size is too small, a smooth reactant flow may not be formed in the catalyst, and thus a pressure difference may be generated in the ammonia inlet, thereby reducing the reaction efficiency. If the median value of the pore size is too large, the specific surface area of the catalyst may decrease, the contact area between the reactant and the catalyst may decrease, and thus the reaction efficiency may decrease.
[0051] Furthermore, within the above range, the amount of noble metal ruthenium supported can be minimized, and at the same time, the efficiency of the ammonia decomposition reaction can be improved, and the life of the catalyst can be increased.
[0052] According to one embodiment, the support may be an inorganic oxide structure. More specifically, the inorganic oxide may be an inorganic oxide containing one or more elements selected from silicon, zirconium, aluminum and cerium.
[0053] According to one embodiment, the first metal may be included in an amount of: about 0.01 parts by weight to about 0.5 parts by weight; or more than about 0.01 parts by weight, or more than about 0.05 parts by weight, or more than about 0.1 parts by weight, and less than about 0.5 parts by weight, or less than about 0.4 parts by weight, or less than about 0.35 parts by weight, or less than about 0.3 parts by weight, based on 100 parts by weight of the carrier and the catalytically active component.
[0054] If the content of the first metal is too small, the efficiency of the ammonia decomposition reaction may decrease. If the content of the first metal is too high, in the process of increasing the coating amount to increase the content of the first metal, the pores of the porous catalyst structure may be blocked, and a smooth reactant flow may not be formed in the catalyst. Therefore, a pressure difference may be generated in the ammonia inlet, and thus, the reaction efficiency may be conversely reduced and the cost may increase.
[0055] According to one embodiment, based on 100 parts by weight of the carrier and the catalytically active component, the content of all catalytically active components, i.e., the first metal, the second metal, and the third metal, can be: about 20 parts by weight or less; or about 0.1 parts by weight or more, or about 0.5 parts by weight or more, or about 1 part by weight or more, and about 20 parts by weight or less, less than about 18 parts by weight, or about 15 parts by weight or less, or about 12 parts by weight or less.
[0056] If the content of the catalytically active component is too low, the active sites of the ammonia decomposition reaction may be reduced, and thus, the efficiency of the ammonia decomposition reaction may be reduced. If the content of the catalytically active component is too high, the pores of the porous catalyst structure may be blocked and a smooth reactant flow may not be formed in the catalyst. Therefore, a pressure difference may be generated in the ammonia inlet, whereby the reaction efficiency may be conversely reduced.
[0057] According to one embodiment, the weight ratio of (second metal): (third metal) can be: about 1:99 to about 3:7; or about 1:99 or more, or about 2:98 or more, or about 3:97 or more, and about 3:7 or less, or about 25:75 or less.
[0058] As described above, among the catalytically active components, ruthenium is known to directly mediate the ammonia decomposition reaction, and lanthanum, aluminum, cerium, etc. can be used as a promoter.
[0059] Since the ruthenium that directly mediates the ammonia decomposition reaction is attached to the acid sites on the surface of the inorganic oxide support, the acid sites should be evenly distributed on the surface of the inorganic oxide support so that the ruthenium can be evenly dispersed on the surface of the support.
[0060] However, the inorganic oxide structure used as a carrier is usually heat-treated at a high temperature of about 900°C or above to ensure strength. During such heat treatment, the acid sites on the surface of the inorganic oxide structure may disappear. Therefore, if ruthenium is directly loaded on an ordinary carrier, it may not be evenly dispersed on the surface of the inorganic oxide structure, but is loaded in the form of large particles. As a result, the surface area of ruthenium on the catalyst surface becomes narrower and the efficiency of the ammonia decomposition reaction may also be reduced.
[0061] In the composite metal oxide containing the third metal as described above, the acid sites of the third metal can be uniformly distributed on the surface, and therefore, ruthenium can be uniformly dispersed and supported, and the surface area of ruthenium on the catalyst surface can be enlarged.
[0062] The second metal can be present in the oxide lattice of the third metal in a stable state and can be used to assist the smooth progress of nitrogen-nitrogen recombination during the ammonia decomposition reaction. In addition, the second metal can isolate the reactive sites formed by ruthenium bound to the acid sites of the third metal to prevent the aggregation of adjacent ruthenium when the ammonia decomposition reaction is carried out, thereby increasing the life of the catalyst.
[0063] In this regard, it may be preferred that the weight ratio of the second metal to the third metal may be maintained within the above range.
[0064] According to one embodiment, the first metal may be included in an amount of: about 0.1 wt % to about 10 wt %; or about 0.1 wt % or more, or about 0.5 wt % or more, or about 1.0 wt % or more, or about 1.5 wt % or more, and about 10 wt % or less, or about 7 wt % or less, or about 5 wt % or less, or about 3 wt % or less, based on the total weight of the catalytically active component.
[0065] According to one embodiment, in the composite metal oxide comprising a catalytically active first metal, a second metal, and a third metal, the molar ratio of the first metal may be about 0.1 to about 10, or about 1 to about 5, or about 2 to about 5, the molar ratio of the second metal may be about 0.1 to about 20, or about 0.5 to about 15, or about 1 to 10, and the molar ratio of the third metal may be about 0.1 to about 35, or about 1 to about 30, or about 3 to about 25.
[0066] According to one embodiment, the ammonia decomposition catalyst may be in the form of a hollow cylinder.
[0067] A hollow cylinder refers to a cylindrical shape in which a hole in the shape of a smaller cylinder passing through the center of the cylinder is formed, and a circle, a cylinder, etc. do not necessarily mean a mathematically precise shape.
[0068] Figure 1 The shape of a hollow cylinder of a catalyst according to one embodiment of the present invention is schematically shown.
[0069] Reference Figure 1 , the hollow cylindrical shape can be confirmed.
[0070] According to one embodiment, the diameter of the circular cross-section of the hollow cylinder can be: about 1 mm to about 10 mm; or about 1 mm or more, 2 mm or more, or about 3 mm or more, or about 4 mm or more, and about 10 mm or less, or about 8 mm or less, or about 7 mm or less, or about 6 mm or less.
[0071] If the diameter of the circular cross-section of the hollow cylinder is too large, the catalyst packing density may decrease and the reactant ammonia gas may pass through without sufficient contact with the catalyst, and thus, the reaction efficiency may decrease. If the diameter of the circular cross-section of the hollow cylinder is too small, the catalyst packing density may become too high, and thus, a pressure difference may be generated, thereby reducing the reaction efficiency.
[0072] According to one embodiment, the diameter of the hollow in the hollow cylinder, ie the central hole through the cylinder, may be 0.1 to 0.5 of the diameter of the circular cross section of the cylinder.
[0073] If the diameter of the central hole is too large, the volume of the catalyst structure may increase relatively, and therefore, the amount of catalytically active components introduced into the reactor may decrease relatively, and the mechanical strength of the catalyst structure may deteriorate. If the diameter of the central hole is too small, a pressure difference may occur, thereby reducing the reaction efficiency, or a local cooling site may be generated in the endothermic ammonia decomposition reaction, thereby also reducing the reaction efficiency.
[0074] According to one embodiment, in the catalyst, the support includes a substrate including alumina and a silica layer formed on the alumina, wherein the catalytically active component is contained in the catalyst layer formed on the silica layer.
[0075] If the catalyst has such a structure, the catalytically active components can be coated not only on the surface of the carrier but also on the internal pores, thereby improving the dispersion of the catalyst and thus showing high reaction activity even with a small amount of the catalytically active components.
[0076] Meanwhile, the above catalyst can be prepared by the following method.
[0077] First, a ruthenium salt aqueous solution is prepared. Among them, as the ruthenium salt aqueous solution, there can be mentioned a ruthenium fluoride aqueous solution, a ruthenium chloride aqueous solution, a ruthenium nitrate aqueous solution, a ruthenium sulfate aqueous solution, a perruthenate ion aqueous solution, and the like.
[0078] Furthermore, La-ceria powder or La-alumina powder is added thereto, and alkaline conditions are generated using ammonia water, etc. It is filtered and washed, and dried in an oven at about 100° C. to about 150° C. for about 6 hours to about 20 hours to obtain a powder.
[0079] Distilled water was added to the obtained powder, zirconium oxide balls were added, and stirred in a drum to prepare a slurry.
[0080] In the slurry solution, the carrier is soaked, and then the remaining solution is completely removed using an air gun, and dried in an oven at about 100° C. to about 150° C. for about 6 hours to about 20 hours. The amount of the coated catalytic active component is weighed to confirm, and the process of coating the slurry solution is further repeated three times, thereby obtaining a supported catalyst in which the above-mentioned first, second and third metals are supported on the carrier.
[0081] Meanwhile, the supported catalyst prepared by the above method may be directly used as an ammonia decomposition catalyst, or may be calcined or reduced and used as an ammonia decomposition catalyst.
[0082] In the calcination and reduction, calcination and reduction conditions commonly used in the technical field to which the present invention pertains may be used, such as treating the obtained catalyst with hydrogen at a temperature of about 300° C. to about 400° C.
[0083] In addition, according to the present disclosure, there is also provided an ammonia decomposition method, comprising performing an ammonia decomposition reaction in the presence of any of the above-mentioned ammonia decomposition catalysts.
[0084] In the ammonia decomposition method according to one embodiment of the present invention, in addition to using the catalyst according to one embodiment of the present invention, reaction conditions commonly used in the technical field to which the present invention belongs may also be used.
[0085] According to one embodiment of the present invention, the ammonia decomposition reaction can be carried out under the following temperature conditions: about 400°C to about 550°C; or above about 400°C, or greater than about 400°C, or above about 420°C, and below about 600°C, or below about 550°C or below about 530°C.
[0086] According to another embodiment, the ammonia decomposition reaction can be carried out before the actual reaction, after purging with an inert gas.
[0087] Furthermore, in the reaction, there is no particular limitation on the form of the reactor, and a suitable form of reactor can be selected and used, which can pass ammonia gas into the catalyst of the above-mentioned shape and allow the catalyst to directly contact the reactant.
[0088] Beneficial Effects
[0089] According to the present disclosure, an ammonia decomposition catalyst having high ammonia decomposition efficiency is provided.
[0090] According to the present disclosure, an ammonia decomposition method using the ammonia decomposition catalyst is also provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0091] Figure 1 The shape of a hollow cylinder of a catalyst according to one embodiment of the present invention is schematically shown.
[0092] Figures 2 to 4 are photographs showing catalysts according to Examples and Comparative Examples.
[0093] Figure 5 and Figure 6 These are images of the catalysts prepared in Comparative Examples 4 and 5, respectively.
[0094] Figure 7 is a SEM image of the catalyst prepared in Example 1.
[0095] Figure 8 and Fig. 9 They are SEM images of the catalysts prepared in Comparative Examples 4 and 5, respectively.
[0096] Fig.10 is a SEM-EDS image of the catalyst prepared in Example 1.
[0097] Fig.11 and Fig.12 They are the SEM-EDS images of the catalysts prepared in Comparative Examples 4 and 5, respectively. DETAILED DESCRIPTION
[0098] Hereinafter, the functions and effects of the present invention will be explained in detail through specific embodiments of the present invention. However, these embodiments are presented only as illustrations of the present invention, and the scope of rights of the present invention is not determined thereby.
[0099] <Example>
[0100] Examples 1 to 5 and Comparative Example 1
[0101] As a source of the metal component, LaCeria synthesized by coprecipitation or commercial LaAlOx (material: LaAlOx; manufacturing company: Sasol; product name: SCFa-145 / L4) was used.
[0102] The material was added to distilled water and stirred at 300 rpm for 30 minutes, then, considering the content of each metal element in the catalytically active component, ruthenium chloride hydrate was added and stirred for an additional 30 minutes. The pH was adjusted to 9 with ammonia water, and then stirred for 18 hours using a stirrer and a magnetic bar. It was filtered and washed with water until the filtered liquid became neutral, placed in an oven at 110°C and dried for about 6 hours to obtain a powder.
[0103] 18 g of the powder obtained above was put into a grinding device, and 300 g of zirconia balls with a diameter of 3 mm and 60 g of zirconia balls with a diameter of 5 mm were used, and ball-milled in a drum at 200 rpm for 6 hours to control the particle size.
[0104] Thereafter, 79.2 g of distilled water and 1.8 g of boehmite were added and stirred in a drum at 200 rpm for 6 hours. In order to dissolve the boehmite and use it as a binder, the pH was adjusted to 3.5 with a 60% nitric acid solution.
[0105] In this solution, about 50 g of a ceramic hollow cylinder including a silica coating formed on an alumina substrate (material: ceramic ring; manufacturing company: Saint-Gobain NorPro; product name: SA5518) was added as a carrier and coated, and then, the remaining solution was removed using an air gun.
[0106] It was placed in an oven at about 110°C and dried for about 6 hours. Drying and coating were repeated until 10% by weight of the coated catalyst became powder. As a result, a shaped catalyst in which the catalyst was coated on the surface of the ceramic hollow cylinder was obtained.
[0107] The metal components in the obtained catalyst material were analyzed by ICP-OES, and the structural changes of the support were confirmed by Hg porosity.
[0108] Figure 2 is an image of the catalyst prepared in Example 1. Figure 2 , a hollow cylindrical catalyst could be confirmed.
[0109] Figure 7 : is an SEM image of the catalyst prepared in Example 1. In the SEM image of the catalyst of Example 1, in addition to the black background, white, light gray, and dark gray can be observed. They correspond to the dark gray alumina substrate, the light gray silica layer, and the white catalyst layer, respectively, and the layered structure of the catalyst according to one embodiment of the present invention can be clearly confirmed by them, the structure comprising: a substrate including alumina; a silica layer formed on the alumina; and a catalyst layer formed on the silica layer.
[0110] Fig.10 is a SEM-EDS image of the catalyst prepared in Example 1. In the SEM-EDS image, the distribution of each element of ruthenium, lanthanum and cerium in the catalyst can be confirmed, specifically, the content of ruthenium as the main active site of the catalyst is low in the entire catalyst and is light in color, but it can be clearly confirmed that it is uniformly dispersed throughout the catalyst.
[0111] Comparative Example 2 and Comparative Example 3
[0112] The same process as in Example 1, Example 2 and Comparative Example 1 was performed except that no supporting was performed, and the obtained powder itself was molded to prepare a catalyst.
[0113] Figure 3 and Figure 4 The following are photos of unsupported catalysts prepared according to Comparative Example 2 and Comparative Example 3, respectively.
[0114] Comparative Example 4
[0115] The same process as in Example 1 was performed to obtain a spherical supported catalyst, except that i) spherical alumina was used as a carrier, and ii) potassium was added as an accelerating component.
[0116] Ru(0.5) / Al2O3; in the final catalyst, the ruthenium content is 0.5 wt%
[0117] Comparative Example 5
[0118] The same process as in Example 1 was performed to obtain a spherical supported catalyst, except that spherical alumina was used as the carrier.
[0119] Ru(1.5) / Al2O3; in the final catalyst, the ruthenium content is 1.5 wt%
[0120] Figure 5 and Figure 6 The images are respectively of the catalysts prepared in Comparative Examples 4 and 5. Figure 5 and Figure 6 , it can be confirmed that the spherical supported catalyst.
[0121] Figure 8 and Fig. 9 4 and 5 are SEM images of the catalysts prepared in Comparative Examples 4 and 5, respectively. In the SEM image of the catalyst prepared in Comparative Example, light gray and dark gray can be observed in addition to the black background. They are confirmed to be the dark gray alumina substrate and the light gray catalyst layer, respectively.
[0122] Fig.11 and Fig.12They are SEM-EDS images of the catalysts prepared in Comparative Examples 4 and 5. In SEM-EDS, the distribution of each element such as ruthenium, lanthanum and potassium can be confirmed, and specifically, it can be clearly confirmed that the main active site of the catalyst, ruthenium, is distributed only on the catalyst surface.
[0123] The information of the obtained catalysts is summarized in Table 1 below.
[0124] [Table 1]
[0125]
[0126]
[0127] *In the empirical formula, the numerical coefficients represent the molar ratio of each element.
[0128] Pore characteristics analysis
[0129] The pore characteristics of the catalysts prepared in Examples and Comparative Examples were analyzed according to the mercury intrusion porosimeter (manufacturer: Micromeritics; model name: AutoPore V) according to the mercury intrusion method.
[0130] An appropriate amount of sample is put into a sample cell without a separate pretreatment process, and then, pressurized at 0.2 psi to 33,000 psi to force mercury into catalyst pores, and the pore volume is measured. The median of the values obtained by the analysis is used as the average diameter.
[0131] [Table 2]
[0132]
[0133] Ammonia decomposition reaction
[0134] 3 g of each of the catalysts prepared in Examples and Comparative Examples was filled in an OD 1 / 2" reactor, and the temperature was raised to 350°C using nitrogen, and then a hydrogen / nitrogen mixed gas (hydrogen 50% by volume) was flowed at the corresponding temperature for about 1 hour for reduction treatment.
[0135] The reduced catalyst was purged in a nitrogen atmosphere at about 350°C for about 30 minutes, and while 99.99% ammonia gas was flowing at 10 sccm, the temperature of the reaction system was raised to about 500°C, and the ammonia decomposition rate was analyzed every 50°C.
[0136] The results of the analysis are summarized in Table 3 below.
[0137] [Table 3]
[0138]
[0139] For the conversion rate, the outlet gas discharged from the reactor was analyzed by GC, the ratio (n) of the volume of NH 3 to the volume of the entire discharged gas was calculated, and the conversion rate was calculated as follows: Conversion rate = (1-n) / (1+n).
[0140] For the pressure difference characteristics of the catalyst, pressure transmitters are installed at the front and rear ends of the reactor to measure the pressure and calculate the pressure difference between the front / rear ends.
[0141] The catalyst layer temperature difference is the temperature difference between the temperature of the furnace for heating the reactor and the internal temperature of the catalyst layer, and is measured by placing a thermocouple (TC) at the center of the catalyst layer.
[0142] Regarding the catalyst strength, the compressive strength was measured using a pressure sensor (FGN-50B, SHIMPO) when crushing a target sample, the measurement was repeated 20 times for each example, and the average value is shown.
[0143] As shown in Table 3, the catalyst according to the embodiment of the present disclosure has a very high ammonia conversion rate and a small pressure difference between the front end and the rear end of the reactor. This means that the gas flow in the catalyst-filled part of the reactor is very smooth.
[0144] Furthermore, it was confirmed that in the case of Examples, the catalyst strength was high and the catalyst layer temperature difference was very small.
[0145] It can be confirmed that in the case of the comparative example, the ammonia conversion rate does not satisfy the example, and a constant pressure difference is generated at the front and rear ends of the reactor. This means that the gas flow in the catalyst-filled part of the reactor is not smooth.
[0146] In some comparative examples, the catalyst strength is low, in which case it is considered that the catalyst located at the lower portion of the catalyst-filled portion cannot withstand the weight and pressure to break, and the catalyst-filled portion may collapse.
[0147] Furthermore, it can be confirmed that the comparative example has a large catalyst layer temperature difference compared to the embodiment, and therefore, when the catalytically active material is densely packed, the reaction (absorption of heat) may occur rapidly, significantly reducing the temperature at the center of the catalyst-packed portion, thereby significantly reducing the reaction activity.
Claims
1. An ammonia decomposition catalyst comprising A carrier and a catalytically active component supported on the carrier, in, The catalytically active component comprises i) ruthenium (Ru) as a first metal; ii) lanthanum (La) as a second metal; and iii) one or more of aluminum (Al) and cerium (Ce) as a third metal, and The catalyst has a porosity of more than 25%.
2. The ammonia decomposition catalyst according to claim 1, wherein The median pore size is 50 μm to 150 μm.
3. The ammonia decomposition catalyst according to claim 1, wherein The support is an inorganic oxide structure.
4. The ammonia decomposition catalyst according to claim 1, wherein The first metal is included in an amount of 0.01 parts by weight to 0.5 parts by weight based on 100 parts by weight of the carrier and the catalytically active component.
5. The ammonia decomposition catalyst according to claim 1, wherein The catalytically active component is included in an amount of 20 parts by weight or less, based on 100 parts by weight of the carrier and the catalytically active component.
6. The ammonia decomposition catalyst according to claim 1, wherein The weight ratio of the second metal:the third metal is 1:99 to 3:
7.
7. The ammonia decomposition catalyst according to claim 1, wherein The first metal is contained in a content of 0.1 wt % to 10 wt % based on the total weight of the catalytically active component.
8. The ammonia decomposition catalyst according to claim 1, wherein The catalyst is in the form of a hollow cylinder.
9. The ammonia decomposition catalyst according to claim 8, wherein The diameter of the circular cross section of the hollow cylinder is 1 mm to 10 mm.
10. The ammonia decomposition catalyst according to claim 8, wherein The diameter of the hollow is 0.1 to 0.5 of the diameter of the circular cross section of the cylinder.
11. The ammonia decomposition catalyst according to claim 1, wherein The support includes a substrate including aluminum oxide and a silicon dioxide layer formed on the aluminum oxide, and The catalytically active components are contained in a catalyst layer formed on the silicon dioxide layer. 12 . An ammonia decomposition method, comprising carrying out a decomposition reaction of ammonia in the presence of the ammonia decomposition catalyst according to claim 1 .
13. The method for decomposing ammonia according to claim 12, wherein: The method is carried out at 400°C to 600°C.
Citation Information
Patent Citations
A multifunctional cooking tools
KR1020230018962A
Control method for server providing block puzzle with customized quiz difficulty for user level
KR1020230096826A